ORGANIZING RATIONAL FOOD FOR CHILDREN ENGAGED IN CPORT TYPE - Khayitov Javokhir Bakhodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
A chess player, who is considered a mental sport, needs to know what nutrients he needs for his mental activity. Proper rational nutrition is very important for a chess player. A person engaged in light physical or mental work should consume 3000-3200 calories per day. Overeating is harmful. Body weight should be monitored regularly.